A Multimodal Discourse Analysis on Street Graffities about Indonesian Police - Rifpan Putra Afriansyah; Eva Tuckyta Sari Sujatna; Nani Darmayanti (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The purpose of this writing is to uncover how graffiti can multimodally represent Indonesian police and create ideology through the use of its textual and visual element. This writing is descriptive qualitative research with multimodal discourse analysis approach. The data of this research are collected through the internet, as the real graffities have been erased from the real-life locations. The data of this research consist of virtual images and sentences of the graffiti that have been documented. The data are analysed through the use of Gunther Kress and Theo van Leeuwen’s multimodal discourse analysis theory of the representational meta-functions, and Michael Halliday’s ideational meta-functions. The analysis is divided into textual and visual analysis. The result of the analysis shows that the graffities represented ideologies that Indonesian police is easily corrupt, enemy of the people, and does not accept critique from the public by the use of specific visuals and words. The graffities that are used as the data of this research are forms of the creators’ ideologies toward Indonesian police.